2015
DOI: 10.1007/s11368-015-1305-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enclosure time on the community composition of methanotrophs in the soils of the Inner Mongolia grasslands

Abstract: Purpose Despite the great number of studies about methane uptake and its response to grazing in the Inner Mongolia grasslands, only a few focused on the methanotrophic composition. This study aimed to investigate the methanotrophic community structure and abundance, then to analyze the abiotic driving factors of methanotrophic community structure in different enclosed times in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
5
8
0
Order By: Relevance
“…In our study, soil PH was acid in this region with highest in PSM, and lowest in PSME, which was similar to the research from forests of Uruguay demonstrating that soil pH in excluded area was lower than in grazed area (Etchebarne & Brazeiro, 2016). However, previous study from Inner Mongolia grasslands finding that soil pH increased and became more neutral with the increase of enclosure time (Ma et al, 2016). What's more, we further found that PSME could increase soil nutrients significantly than PSM, including soil total C, total N, total P and available N contents (P < 0.05), which was agreement with the studies about grassland from Xiong et al (2016) and Gebregergs et al (2019).…”
Section: Effects Of Afforestation Combined With Enclosure Management On Soil Propertiessupporting
confidence: 89%
“…In our study, soil PH was acid in this region with highest in PSM, and lowest in PSME, which was similar to the research from forests of Uruguay demonstrating that soil pH in excluded area was lower than in grazed area (Etchebarne & Brazeiro, 2016). However, previous study from Inner Mongolia grasslands finding that soil pH increased and became more neutral with the increase of enclosure time (Ma et al, 2016). What's more, we further found that PSME could increase soil nutrients significantly than PSM, including soil total C, total N, total P and available N contents (P < 0.05), which was agreement with the studies about grassland from Xiong et al (2016) and Gebregergs et al (2019).…”
Section: Effects Of Afforestation Combined With Enclosure Management On Soil Propertiessupporting
confidence: 89%
“…In our study, soil PH was acid in this region with highest in PSM, and lowest in PSME, which was similar to the research from forests of Uruguay demonstrating that soil pH in excluded area was lower than in grazed area (Etchebarne & Brazeiro, 2016). However, previous study from Inner Mongolia grasslands finding that soil pH increased and became more neutral with the increase of enclosure time (Ma et al, 2016). What's more, we further found that PSME could increase soil nutrients significantly than PSM, including soil total C, total N, total P and available N contents (P < 0.05), which was agreement with the studies about grassland from Xiong et al (2016) and Gebregergs et al (2019).…”
Section: Effects Of Afforestation Combined With Enclosure Management supporting
confidence: 89%
“…The temperate grassland is a CH 4 sink (Geng et al, 2010). Consistently, methanotrophs are highly abundant in the temperate grasslands, with 10 7 –10 8 pmoA gene copies per gram of soil and USC‐γ as the main methanotrophic cluster (T. Ma et al, 2015). Methanotrophic abundance increased with lower soil moisture content, which facilitates more CH 4 and O 2 diffusion into soil amenable for the proliferation of methanotrophs.…”
Section: Functional Microbial Communities In a Changing Worldmentioning
confidence: 93%